85.0k views
5 votes
Find the solution the each of the following first order linear differential equations:

a) xy' -4y = 2 x^6

b) y' - 5y = 4e^7x

c) dy/dx + 2y = 2/(1+e^4x)

d) 1/2 di/dt + i = 4cos(3t)

User Mneute
by
5.7k points

1 Answer

5 votes

Answer:

a.
y=(2)/(3)x^7+cx^4

b.
y=2e^(7x)-ce^(5x)

c.
y=e^(-2x)arctan(e^(2x))+ce^(-2x)

d.
i=e^(-2t)\left((8\left(3e^(2t)\sin \left(3t\right)+2e^(2t)\cos \left(3t\right)\right))/(13)+C\right)

Explanation:

a) xy' -4y = 2 x^6


xy'-4y=2x^6\\y'-(4)/(x)y=2x^5\\p(x)=(-4)/(x)\\Q(x)=2x^5\\\mu(x)=\int P(x)dx=\int (-4)/(x)dx=Ln|x|^(-4)\\y=e^(-\mu(x))\int {e^(\mu(x))Q(x)dx}\\y=x^4 \int {x^(-4)2x^6}dx\\y=(2)/(3)x^7+cx^4

b) y' - 5y = 4e^7x


y'-5y=4e^(7x)\\p(x)=-5\\Q(x)=4e^(7x)\\\mu(x)=\int P(x)dx=\int-5dx=-5x\\y=e^(-\mu(x))\int {e^(\mu(x))Q(x)dx}\\y=e^(5x)\int {e^(-5x)4e^(7x)}dx\\y=2e^(7x)-ce^(5x)

c) dy/dx + 2y = 2/(1+e^4x)


(dy)/(dx)+2y=(2)/(1+e^(4x))\\p(x)=2\\Q(x)=(2)/(1+e^(4x))\\\mu(x)=\int P(x)dx=\int 2dx=2x\\y=e^(-\mu(x))\int {e^(\mu(x))Q(x)dx}\\y=e^(-2x)\int {e^(2x)(2)/(1+e^(4x))}dx\\y=e^(-2x)arctan(e^(2x))+ce^(-2x)

d) 1/2 di/dt + i = 4cos(3t)


(1)/(2)(di)/(dt)+i=4cos(3t)\\(di)/(dt)+2i=8cos(3t)\\p(t)=2\\Q(t)=8cos(3t)\\\mu(t)=\int P(t)dt=\int 2dt=2t\\i=e^(-\mu(t))\int {e^(\mu(t))Q(t)dt}\\i=e^(-2t)\int {e^(2t)8cos(3t}dt\\i=e^(-2t)\left((8\left(3e^(2t)\sin \left(3t\right)+2e^(2t)\cos \left(3t\right)\right))/(13)+C\right)

User William Yeh
by
5.4k points